Introduction: Sustainability in the coastal zone - Heidkamp, C.P.; Morrissey, J. (Towards Coast. Resil. and Sustainability, 2018)
Coastal areas provide many co-benefits associated with their natural infrastructure, facilitating activities such as fishing, industry, tourism and transportation, for instance (Barragán & de Andrés, 2015; Sutton-Grier, Wowk & Bamford, 2015). Despite occupying a relatively small percentage of the Earth's land surface, the value of the ecosystems’ services of coastal areas is more than one-third of the total for the globe (Barbier et al., 2011; Barragán & de Andrés, 2015). However, while the goods and services provided by coastal ecosystems are essential for economic and social well-being (Mavrommati, Bithas & Panayiotidis, 2013), coastal ecosystems are increasingly at risk. As a direct result of intensive resource use and of concentrations of population, coastal ecosystems increasingly demonstrate direct and adverse impacts of human activities (Swaney et al., 2012). Increasing population growth, movement of populations towards the coast and the increase in coastal development have led to an increase in pressure on, and degradation of, coastal ecosystems (Duxbury & Dickinson, 2007). For large coastal cities, interactions between human activities and coastal systems are intensified due to population density effects and associated economic activities (Mavrommati et al., 2013). In many parts of the world, coastal natural habitats are declining and overexploited coastal resources are dwindling, with associated impacts on ecosystems and on the livelihoods dependent on these (Mee, 2012). © 2019 selection and editorial matter, C. Patrick Heidkamp and John Morrissey.
Keywords: Coastal development; Coastal ecosystems; Coastal resources; Coastal zones; Economic activities; Economics; Ecosystems; Increase in pressure; Population densities; Population growth; Population statistics; Social well-being; dept.egm